A Case Report on Rhino-Cerebral Mucormycosis With Acute Respiratory Failure - Ms. Sakshi R. Thool, Sarika Selsurkar, Ashish Bhagat (Drugs and Cell Therapies in Hematology, 2021)
Rhino cerebral mucormycosis is an invasive, opportunistic fungal infection usually seen in immunocompromised patients, and particularly in the setting of diabetes or immune deficiency. It is assumed that the port of entry is colonization of the nasal mucosa, allowing the fungus to spread via the paranasal sinuses into the orbit. Patient history: A 50 year male admitted in AVBRH hospital on dated 18/5/21 with the chief complete of fever, nasal blockage since 1 month, swelling around eye, right side blurred vision, one sided facial pain headache nasal sinus, congestion, one sided facial swelling, cough, breathlessness weakness. Fungal infection and watery discharge from eye. Clinical finding: The patient had done all necessary investigations by physician order. Medical Management: Patient was treated with oxygen therapy, antiemetic, antifungal and antibiotics medication. Nursing management: Administered fluid replacement i.e. RL, oxygen therapy, nebulizer, monitor vital sign hourly . Conclusion: Timely treatment and management of bilateral maxillary ethmoid and sinusitis fungal mucormycosis.